Peranan Teknologi Pendidikan Dalam Peningkatan Kualitas Pembelajaran - Asmadi1, Soraya Zairina; Nasution, Wahyuddin Nur; Padli Nasution, Muhammad Irwan (Universitas Pahlawan Tuanku Tambusai, 2025)
The advancement of digital technology has brought a major transformation in the world of education. Educational technology not only plays a role as a tool, but has also become a catalyst in improving the quality of learning. This article aims to examine the definition of educational technology, its form of utilization, its strategic role in improving the quality of learning, and the challenges of its implementation in schools. The method used is a literature study with a qualitative descriptive approach. The results of the discussion showed that educational technology is able to increase the effectiveness, efficiency, and attractiveness of learning, as well as encourage student participation and shape 21st century skills. However, the implementation of educational technology still faces obstacles such as limited infrastructure, teacher competence, and digital literacy of students. Therefore, it takes the collaboration of all parties to maximize its potential.